Optical and Microphysical Properties of the Aerosol Field over Sofia, Bulgaria, Based on AERONET Sun-Photometer Measurements - Tsvetina Evgenieva; Ljuan Gurdev; Eleonora Toncheva; Tanja Dreischuh (Atmosphere, 2022)
An analysis of the optical and microphysical characteristics of aerosol passages over Sofia City, Bulgaria, was performed on the basis of data provided by the AErosol RObotic NETwork (AERONET). The data considered are the result of two nearly complete annual cycles of passive optical remote sensing of the atmosphere above the Sofia Site using a Cimel CE318-TS9 sun/sky/lunar photometer functioning since 5 May 2020. The values of the Aerosol Optical Depth (AOD) and the Ångström Exponent (AE) measured during each annual cycle and the overall two-year cycle exhibited similar statistics. The two-year mean AODs were 0.20 (±0.11) and 0.17 (±0.10) at the wavelengths of 440 nm (AOD440) and 500 nm, respectively. The two-year mean AEs at the wavelength pairs 440/870 nm (AE440/870) and 380/500 nm were 1.45 (±0.35) and 1.32 (±0.29). The AOD values obtained reach maxima in winter-to-spring and summer and were about two times smaller than those obtained 15 years ago using a hand-held Microtops II sun photometer. The AOD440 and AE440/870 frequency distributions outline two AOD and three AE modes, i.e., 3 × 2 groups of aerosol events identifiable using AOD–AE-based aerosol classifications, additional aerosol characteristics, and aerosol migration models. The aerosol load over the city was estimated to consist most frequently of urban (63.4%) aerosols. The relative occurrences of desert dust, biomass-burning aerosols, and mixed aerosols were, respectively, 8.0%, 9.1% and 19.5%.